COVID -19 pandemic is a worldwide typical biopsychosocial crisis (Journal of Ideas in Health, 2020)
Since December 2019, the world has been stunned by the speed of the spread of the COVID-19. All the possibilities were likely, except that people would hide in their homes for fear of contracting the disease, as it was very unlikely. The lockdown was imposed severely, and people panicked, and their interest has limited to providing food and caring for health and family. The effect of isolation and the prevention of social interaction was apparent in the individuals' psychological behavior. Unfortunately, the incidence of depression, anxiety, and domestic violence increased, which negatively impact family stability in the short and medium-term. The pathological, psychological, and social impact of COVID-19 imposes a framework for dealing with the pandemic based on the biopsychosocial model.
Keywords: COVID-19, pandemic, Biopsychosocial model, Crisis